The Influence of Financial Literacy, Experienced Regret, and Risk Perception on Investment Decisions in Cryptocurrency - M. Trihudiyatmanto (Jurnal Akuntansi, Manajemen dan Perbankan Syariah, 2024)
Objective - This study aims to demonstrate the influence of financial literacy, experienced regret, and risk perception on cryptocurrency investment decisions in the digital era among students at the Al-Qur'an Science University. Methodology - This is a quantitative study. The population was students at the Al-Qur'an Science University. The sampling technique used was non-probability sampling with a purposive sampling technique using the Slovin formula. The sample size was 388 respondents. Data analysis included descriptive analysis, data quality testing, the F-test, classical assumption testing, multiple linear regression analysis, hypothesis testing, and the coefficient of determination test. Data collection in this study used a questionnaire with a Likert scale format. The collected data were then analyzed using SPSS 30.0. Results - The study shows that the variables of financial literacy, financial behavior, and risk perception have a positive effect on investment decisions, while experienced regret has no effect on investment decisions. This is evidenced by the results of financial literacy, which had a t-test of 3.009 with a significance value of 0.003 < 0.05. Risk perception had a t-test of 3.418 with a significance value of 0.001 < 0.05. And experienced regret had a t-test of -0.618 with a significance value of 0.537 > 0.05. Limitations – This study involved data collection, which may have inaccurate respondents' opinions in the questionnaire. Future research agenda – Respondents need to be assisted when completing the questionnaire to ensure accuracy and understanding of their circumstances. This is expected to broaden the scope of the research area.